FMR1 Disorders: Basics of Biology and Therapeutics in Development - Drew A. Gillett; Helene Tigro; Yuan Wang; Zucai Suo (Cells)
Fragile X Syndrome (FXS) presents with a constellation of phenotypes, including trouble regulating emotion and aggressive behaviors, disordered sleep, intellectual impairments, and atypical physical development. Genetic study of the X chromosome revealed that substantial repeat expansion of the 5′ end of the gene fragile X messenger ribonucleoprotein 1 (FMR1) promoted DNA methylation and, consequently, silenced expression of FMR1. Further analysis proved that shorter repeat expansions in FMR1 also manifested in disease at later stages in life. Treatment and therapy options do exist, but they only manage symptoms. Up to now, no cure for FMR1 disorders exists. In this review, we aim to provide an overview of FMR1 biology and the latest research focused on developing therapeutic interventions that can potentially prevent and/or reverse FXS.